Quality seed: an innovative sorting technique to sustainable, uniform and effective seedling establishment in nursery for system of rice intensification - Bashar, Zubairu Usman; Wayayok, Aimrun; Mohd Soom, Mohd Amin; Mahadi, Muhammad Razif (Canadian Center of Science and Education, 2014)
One of the major problems of adapting the System of Rice Intensification (SRI) techniques is knowledge shortfall on the technical skills for processing quality seeds to achieve uniform seedling establishment in the nursery and quick seedling recovery in the puddled field. Therefore, this study aimed to create suitably seed sorting technique leading to vigorous and quality seedlings to improve potentiality of SRI nursery and reduce seedlings transplanting shock. It involved sorting of MR219 rice seeds the most popular grown variety in Malaysia in NaCl solutions of 0 g/L(water alone), 40 g/L, 60 g/L, 80 g/L, 100 g/L and 120 g/L, respectively. The experiment revealed that 100% germination after ten days was obtained from the sunken MR219 seeds collected in 80 g/L of NaCl solution. These values reported a decrease in germination (85%) with increasing NaCl concentration (120 g/L), with least germination vigor of 42% in water alone (0 g/L) 3 days. The percentage of sprouting proved to be high from the sunken seeds obtained in 80 g/L with 100% sprouting success rate. A decrease in percentage (70%) has been revealed with increasing NaCl concentration from the seeds obtained in 120 g/L and also when it was reduced to 40 g/L which reported 65% of the sprouting rate. Therefore, this technical information serves as benchmark to practicing farmers that high concentration in NaCl not only reduces the percentage of viable seeds but also increases seedling preparation cost as well as the entire production cost.